Konsumsi Fast Food dan Kuantitas Tidur Sebagai Faktor Risiko Obesitas Siswa SMA Institut Indonesia Semarang - Angga Wijaya Nugraha; Agus Sartono; Erma Handarsari (Universitas Muhammadiyah Semarang, 2019)
Obesity is a condition when there is excess body fat accumulation, so that a person's BMI is > 25 kg/????2 and is a risk factor for various diseases. In 2016 the rate of obesity in adolescents in Central Java was 11.19% and in Semarang City was 11.09%, potentially to become a public health problem. The frequency of fast food consumption and sleep duration can affect the occurrence of obesity. The purpose of this study was to determine the frequency of fast food consumption and quantity of sleep as a risk factor for the incidence of obesity in high school students at Institut Indonesia Semarang. The type of this research is case control. Samples numbered 60 samples consisting of 30 cases and 30 controls. Sampling using random sampling technique. Frequency of fast food consumption with food frequency questionnaire and quantity of sleep with sleep timing questionnaire. Obesity is determined by BMI. Risk factor analysis with chi-square test and odds ratio value. The results showed the incidence of obesity 34 students (6.5%). Students who often consume fast food 28 students (46.7%). Students who have short sleep duration are 28 students (46,7%). There is a relationship between the frequency of fast food consumption with the incidence of obesity, with the value of OR 2.259. There is a relationship between the quantity of sleep with the incidence of obesity with the value of OR 3,0. Often consuming fast food and short sleep quantity are risk factors for obesity, each with a large risk of 2,259 and 3 times.Keywords: Obesity, Fast Food Consumption , Sleep Quantity